Word Order in Libyan Arabic - Mohamed Krer (Aljameai, 2023)
Abstract: The main purpose of this paper is to shed some light on word order in Libyan Arabic; one of the least known Arabic varieties in the literature of Arabic syntax. In Libya there are three dialects of Libyan Arabic: eastern, western and southern dialect. In this paper, however, I will focus on the Libyan Arabic spoken in the western part of Libya. The paper will discuss possible word orders in different types of clauses including; root clauses, finite and non-finite embedded clauses. We will see that not all word orders allowed in root clauses are possible in embedded clauses. Word order will also be investigated simple and wh-questions. The strategies followed in forming questions in Libyan Arabic will also be discussed. Each type of clauses studied in this paper will be accounted for by giving the tree-diagram representation within the Minimalist Program.  المستخلص:الغرض الرئيسي من هذه الورقة هو إلقاء بعض الضوء على ترتيب الكلمات في العربية الليبية ، وهى أحدى أقل اللهجات العربية شهرة في علم اللغة العربي. عدد الدراسات عن هذه اللهجة ضئيل جدا مقارنة باللهجات العربية الأخرى. هناك ثلاث لهجات فرعية في ليبيا: اللهجة الشرقية والغربية والجنوبية الا انني سوف أركز في هذه الورقة على اللهجة المستخدمة في الجزء الغربي من ليبيا. ستناقش الورقة ترتيب الكلمات المحتملة في أنواع مختلفة من الجمل بما في ذلك ؛ جمل جذرية ، جمل محدودة وغير محدودة. سنرى أنه ليست كل تراتيب الكلمات المسموح بها في الجمل الجذرية ممكنة في الجمل المضمنة. سيتم أيضًا التحقق من ترتيب الكلمات في الجمل الاستفهامية.  بالاضافة الى مناقشة الاستراتيجيات المتبعة في تشكيل الجمل الاستفهامية في اللهجة الليبية. سيتم تحليل كل نوع من الجمل التي تمت دراستها في هذه الورقة حسب القواعد المتبعة في نظرية منماليست بروغرام.